Politically Exposed Persons : a Guide on Preventive Measures for the Banking Sector. - Greenberg, Theodore S. (World Bank Publications, 2010)
In recent years, the revelations of grand corruption and the scale of the plunder of state assets has led to greater scrutiny of financial relationships with politically exposed persons (PEPs) and potential money laundering risks associated with these customers. PEPs?individuals who are or have been entrusted with prominent public functions, their family members, and close associates?represent a greater risk because of the possibility that such individuals may abuse their position and influence to accept and extort bribes and misappropriate state assets. Implementation of an effective PEPs reg.